Digitalisierungsschub in Firmen während der Corona-Pandemie; Digitalisation in companies: The COVID-19 Pandemic as a push factor - Lutz Bellmann; Pauline Bourgeon; Christina Gathmann; Christian Kagerl; David Marguerit; Ludivine Martin; Laura Pohlan; Duncan Roth (Wirtschaftsdienst, 2021)
Durch die Corona-Pandemie haben digitale Technologien in Unternehmen an Bedeutung gewonnen. Auf Basis einer Betriebsbefragung des Instituts für Arbeitsmarkt- und Berufsforschung untersuchen die Autor:innen, ob Unternehmen vermehrt in digitale Technologien investiert haben und welche Rolle dabei die wirtschaftliche Situation gespielt hat. Neben den Investitionen in digitale Technologien haben auch Weiterbildungsaktivitäten in den Betrieben zugenommen. – – This article shows the extent to which companies' investments in digital technologies have increased during the COVID-19 pandemic. Based on a large German company survey conducted by the Institute for Employment Research, the authors examine whether and which companies have invested in different types of digital technologies, how these investments are connected to working from home, and how investments are influenced by the economic situation of companies during the pandemic. The authors also discuss further training activities provided and planned by employers and how those are related to their investments in digital technologies.
Keywords: J24; L23; I18; 330; Epidemie; Coronavirus; Unternehmen; Digitalisierung; Deutschland